DEFENDING ISLAMIC TRADITION: Theological Responses of the Hadrami Majlis Taklim Groups toward the Salafi-Wahabi Preaching Movement in Contemporary Indonesia (JOURNAL OF INDONESIAN ISLAM, 2022)
This article discusses majlis taklim as an informal religious learning group in urban area led by Hadrami descents in Indonesia that functions not only in preaching Islam but also in defending their Islamic traditions and practices toward the criticism of Salafi movement in Indonesia. The data presented here is based on in-depth interview with members and leaders of the group and participant observation. This article argues that Islamic traditions in Indonesia are about knowledge, worldview, values, and mode of behavior for Indonesian Muslims, where the Scripture and the spirit of Scripture is the ultimate reference. In this study, we show how Islamic traditions in Indonesia have been carefully maintained, developed, and transmitted through generations. Despite the strong criticism of Salafi group in urban areas, Islamic traditions have been preserved and disseminated through the majlis taklim groups, including by the Indonesian Hadrami individuals. This study is aimed to look at how Hadrami majlis taklim in the urban area maintains, develops and transmits Islamic tradition to the Muslim community and give theological response to the Salafi group’s attack to their practices. The effort of Hadrami majlis taklim has contributed to the maintaining of religious tolerance in contemporary Indonesia.